The development of a portable Earth's field NMR system for the study of Antarctic sea ice : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Electronics at Massey University - Dykstra, Robin (Massey University, 2001)
A portable Nuclear Magnetic Resonance (NMR) spectrometer based on digital signal processor (DSP) technology has been developed and applied to the study of the structure of Antarctic sea ice. The portability of this system means that external sources of noise can be minimised and remote sites can be investigated. A new sea-ice probe has been developed in conjunction with the spectrometer allowing in-situ measurement of water content, relaxation times and self diffusion. The new probe minimises disturbances to the sea ice sample which have been a problem with previous techniques. The core of the spectrometer consists of a Motorola DSP56303 DSP which controls the NMR experiment under the supervison of a host computer which in this case is a PC laptop. Communication between host and DSP is via either a PCMCIA card or USB interface. DSP software runs the experiment, controls acquisition and performs digital filtering of the NMR data before sending it to the PC for analysis and display. The flexibility of the DSP based core means that this system could be adapted to other control applications with relative ease.
Keywords: Nuclear magnetic resonance; Signal processing; Digital techniques; Microprocessors; Antarctica Sea ice; Analysis